Entry to Tertiary Carbinamines Bearing a gem-Diaryl Group by Copper-Catalyzed Grignard Addition to Cyclic Sulfamidate Imines. - Pitchaiah, Arigala; Kim, Miri; Taek Hwang, In; Lee, Kee-In (Current Organic Synthesis, 2013)
We report a convenient access to tertiary carbinamines bearing a gem-diaryl group by Cu-catalyzed aryl Grignard addition to cyclic sulfamidate imines and sulfamide imines. The synthesis of hetero-functionalized 1,2-ethylene derivatives by ring-opening of the resulting sulfamidates is also described.
Keywords: tertiary carbinamine